2020
DOI: 10.3390/microorganisms9010015
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Invasion Mechanisms and Host Immune Response to Plasmodium vivax Malaria: Trends and Future Directions

Abstract: Plasmodium vivax malaria is a neglected tropical disease, despite being more geographically widespread than any other form of malaria. The documentation of P. vivax infections in different parts of Africa where Duffy-negative individuals are predominant suggested that there are alternative pathways for P. vivax to invade human erythrocytes. Duffy-negative individuals may be just as fit as Duffy-positive individuals and are no longer resistant to P.vivax malaria. In this review, we describe the complexity of P.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 187 publications
0
18
0
Order By: Relevance
“…However, in recent years, it has been demonstrated that Duffy-negative individuals can be infected by P. vivax . This is probably due to other molecules involved in reticulocyte invasion, suggesting that the invasion mechanism is much more complex than believed ( 170 173 ).…”
Section: Blood-stage Vaccinementioning
confidence: 98%
See 1 more Smart Citation
“…However, in recent years, it has been demonstrated that Duffy-negative individuals can be infected by P. vivax . This is probably due to other molecules involved in reticulocyte invasion, suggesting that the invasion mechanism is much more complex than believed ( 170 173 ).…”
Section: Blood-stage Vaccinementioning
confidence: 98%
“…Some RBPs, localized at the apical pole of merozoites, are possibly involved in the alternative invasion pathway of Duffy-negative individuals since they can bind to erythrocytes and have reticulocyte selectivity ( 172 , 173 , 193 , 194 ). Each protein has one specific binding site different from PvDBP.…”
Section: Blood-stage Vaccinementioning
confidence: 99%
“…These DBP vaccine efforts follow a body of research showing the importance of the Duffy glycoprotein on the surface of RBCs [ 41 ] as a receptor for the P. vivax DBP, which is located at the front (apical) end of the merozoite and is known to specifically attach to the cognate RBC receptor prior to invading the host RBC [ 299 , 302 304 ]. Complicating the situation, in the ensuing years, through research in multiple locales, it has become apparent that P. vivax can also invade Duffy negative RBCs by utilizing alternate invasion mechanisms (reviewed in [ 305 , 306 ]).…”
Section: Twenty-first Century—turning Point In Malaria Researchmentioning
confidence: 99%
“…This action raises important issues concerning how P. vivax enters the erythrocytes of Duffy-negative individuals. It has been hypothesized that copy number variation, which is either low expression of DARC in Duffy-negative individuals, binds easily to parasites that carry multiple copies of P. vivax Duffy binding protein (PvDBP), changes in PvDBP1 or duplication in the PvDBP gene created a new entryway and is responsible for the parasites' increased ability to spread [ 97 , 155 ]. Due to this, it is challenging to control and eradicate P. vivax malaria, which highlights the concern that these 'new' P. vivax strains that infect Duffy-negative hosts could spread throughout much of Africa and have severe, significant effects on the general public health and economy.…”
Section: Control Challengesmentioning
confidence: 99%